From 'collapse' to urban diaspora: the transformation of low-density, dispersed agrarian urbanism. (October 2015) - Lucero, Lisa J.; Fletcher, Roland; Coningham, Robin
Abstract: Abstract : In the tropical regions of southern Asia, Southeast Asia and the southern Maya lowlands, the management of water was crucial to the maintenance of political power and the distribution of communities in the landscape. Between the ninth and sixteenth centuries AD, however, this diverse range of medieval socio-political systems were destabilised by climatic change. Comparative study reveals that despite their diversity, the outcome for each society was the same: the breakdown of low-density urban centres in favour of compact communities in peripheral regions. The result of this, an 'urban diaspora', highlights the relationship between the control of water and power, but also reveals that the collapse of urban centres was a political phenomenon with society-wide repercussions.